Another side of the coin: Primary progressive aphasia in Chinese language. (31st December 2021) - Tee, Boon Lead; Tempini, Maria Luisa Gorno; Chen, Ta‐Fu; Lo, Raymond Y.; Wang, Pei‐Ning; Chan, Andrew LT; Chen, Lorinda Li‐Ying Kwan; Wong, Adrian; Yan, Connie TY; Tsoh, Joshua; Lu, Chien Jung
Abstract: Background: Primary Progressive Aphasia (PPA) is a neurodegenerative syndrome that presents with speech and language impairments and is generally classified into three variants: semantic (svPPA), nonfluent/ agrammatic (nfvPPA), and logopenic variants (lvPPA). Current understanding of PPA has been mostly derived from English language patients. Expanding PPA research into non‐English languages encourages language‐specific linguistic‐adapted assessments and enriches our knowledge in linguistic features distinct from English language. This presentation focuses on three Chinese linguistic features that differ from English language: lexical tones, classifier, and logographic script. Chinese is a tonal and classifier language in which tones are lexically contrastive, and classifiers are obligatory to quantify nouns numerally. It also adopts logographic script that has complex visuospatial configurations and weak grapheme‐phoneme correspondence. Method: The CLAP (C hinese L anguageA ssessment for P PA) battery is designed to characterize the neurolinguistics features of Chinese speaking PPA individuals. In CLAP classifier task, participants are asked to spontaneously produce classifiers specific to numerous nouns and presented with multiple choices when failed. To evaluate Chinese writing skills, participants are tasked with dictating 60 Chinese characters of varying lexicality, character frequency, and stroke number. The motor speech function is assessed by multiple repetitions of Chinese characters that differ in articulation places, manners, and tones. Results: The CLAP project enrolled 20 controls and 33 PPA individuals (7 nfvPPA, 10 svPPA, and 16 lvPPA). In classifier task, svPPA and lvPPA scored lower (p<0.01), though lvPPA were more responsive to choices than svPPA (p<0.001). The classifier score significantly correlated with volumetric changes over the left middle, inferior temporal, and fusiform gyri, brain regions typically associated with semantic functions. For orthographic dictation task, all three PPA variants performed worse than controls (p<0.001), and distinctive dysgraphia phenotypes were noted in each variant (svPPA: phonological plausible and perseveration errors; nfvPPA: motoric, radical and morphemic errors; lvPPA: visual and stroke errors, P<0.001). In motor speech task, nfvPPA showed lower performance when tasked with repeating characters that vary in articulation places and tones (p=0.018, p<0.001) but not in articulation manners (p=0.076). Conclusion: The clinical features and assessment strategies for PPA syndrome may vary across languages and should ideally be tailored linguistically.